2013
DOI: 10.1108/17538391311329833
|View full text |Cite
|
Sign up to set email alerts
|

Performance indicators of banks in a total Islamic banking system: the case of Sudan

Abstract: PurposeThe purpose of this paper is to describe the common performance traits of banks operating in a whole Islamic banking system in Sudan. Sudan is among the few economies in which a whole Islamic banking system is in place.Design/methodology/approachNine banks representing the most active and large banks are used as a sample for this analysis. The study applied factor analysis to a large set of financial ratios that are commonly used in financial analysis of banks.FindingsThe study found that six factors ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 15 publications
(13 reference statements)
0
11
1
1
Order By: Relevance
“…Then, the other previous researches conducted by Almunawwaroh and Marliana (2018), Muin (2017), and Sari, Anshori, and Primasari (2018), explain that CAR has a negative and significant effect on profitability (ROA). Those data are different from research's results from Wibowo and Syaichu (2013), Ahmad, Nafees, and Khan (2012), Schiniotakis (2012), Eljelly and Elobeed (2013), and Yusuf and Surjaatmadja (2018) whom find that CAR has a positive and significant effect on profitability (Return on Assets/ROA).…”
Section: Coefficient Of Determinationcontrasting
confidence: 85%
“…Then, the other previous researches conducted by Almunawwaroh and Marliana (2018), Muin (2017), and Sari, Anshori, and Primasari (2018), explain that CAR has a negative and significant effect on profitability (ROA). Those data are different from research's results from Wibowo and Syaichu (2013), Ahmad, Nafees, and Khan (2012), Schiniotakis (2012), Eljelly and Elobeed (2013), and Yusuf and Surjaatmadja (2018) whom find that CAR has a positive and significant effect on profitability (Return on Assets/ROA).…”
Section: Coefficient Of Determinationcontrasting
confidence: 85%
“…Two indicators have been used for measuring banks' profitability (the dependent variable); return on assets (ROA) and return on equity (ROE). ROA is defined as the ratio of net profit after tax divided by total assets (e.g., Lee and Hsieh, 2013;Zaidirina and Lindrianasari, 2015;Yeon and Kim, 2013;Bogdan and Ihnatov, 2014;Tiberiu, 2015;Malichov and Mária, 2015;Ozili and Uadiale, 2017;Javaid and Alalawi, 2018;, and ROE is measured by net profit after tax to shareholders' equity (e.g., Eljelly and Elobeed, 2013;Abbas et al, 2014;Kythreotis, 2014;Jedidia, 2016). As shown in Figure 1, the independent variables are classified in this study into two categories;…”
Section: Literature Reviewmentioning
confidence: 99%
“…Quality of bank management has a positive and significant effect on the Islamic banks' profitability. Eljelly and Elobeed (2013) have shown that only factors such as cost, liquidity and bank size have a positive and significant impact on performance. External factors are insignificant determinants.…”
Section: H1mentioning
confidence: 99%